Umrah Trends in Society: Influencer, Media and the Way to Construct Between Worship and Religious Tourism - Husna, Fathayatul; Sariyanti, Lilis (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
Umrah, which is a form of worship in Islam, has changed practice and meaning in modern society. Currently, modern society interprets Umrah not only as worship but also as religious tourism and places Umrah as a lifestyle practice. This article discusses the trend of Umrah plus tourism in modern society, with a focus on social media and influencers in framing the perspective of society and encouraging people to perform Umrah. Mass media such as Instagram and TikTok play an important role in promoting Umrah travel, both through advertisements, and testimonials from pilgrims who describe the spirituality of the Umrah journey. In addition, influencers or even artists also play an important role in the Umrah trend in modern society, where their reviews and posts about certain Umrah travel will attract people's interest in doing the same. A qualitative approach is used as a method in analyzing content and public perceptions of Umrah as worship and religious tourism. The results of this study show that the role of social media and influencers is not only limited to promotion but also as agents of change in shaping the perception of modern society regarding the meaning of Umrah